Biofunctionalized Structure and Ingredient Mimicking Scaffolds Achieving Recruitment and Chondrogenesis for Staged Cartilage Regeneration - Yang, Zhen; Li, Hao; Tian, Yue; Fu, Liwei; Gao, Cangjian; Zhao, Tianyuan; Cao, Fuyang; Liao, Zhiyao; Yuan, Zhiguo; Liu, Shuyun; Guo, Quanyi (Frontiers in Cell and Developmental Biology, 2021)
It remains scientifically challenging to regenerate injured cartilage in orthopedics. Recently, an endogenous cell recruitment strategy based on a combination of acellular scaffolds and chemoattractants to specifically and effectively recruit host cells and promote chondrogenic differentiation has brought new hope for in situ articular cartilage regeneration. In this study, a transforming growth factor-β3 (TGF-β3)-loaded biomimetic natural scaffold based on demineralized cancellous bone (DCB) and acellular cartilage extracellular matrix (ECM) was developed and found to improve chondral repair by enhancing cell migration and chondrogenesis. The DCB/ECM scaffold has porous microstructures (pore size: 67.76 ± 8.95 μm; porosity: 71.04 ± 1.62%), allowing the prolonged release of TGF-β3 (up to 50% after 42 d in vitro) and infrapatellar fat pad adipose-derived stem cells (IPFSCs) that maintain high cell viability (>96%) and favorable cell distribution and phenotype after seeding onto the DCB/ECM scaffold. The DCB/ECM scaffold itself can also provide a sustained release system to effectively promote IPFSC migration (nearly 2 fold in vitro). Moreover, TGF-β3-loaded on scaffolds showed enhanced chondrogenic differentiation (such as collagen II, ACAN, and SOX9) of IPFSCs after 3 weeks of culture. After implanting the composite scaffold into the knee joints of rabbits, enhanced chondrogenic differentiation was discovered at 1, 2, and 4 weeks post-surgery, and improved repair of cartilage defects in terms of biochemical, biomechanical, radiological and histological results was identified at 3 months and 6 months post-implantation. To conclude, our study demonstrates that the growth factor (GF)-loaded scaffold can facilitate cell homing, migration, and chondrogenic differentiation and promote the reconstructive effects of in vivo cartilage formation, revealing that this staged regeneration strategy combined with endogenous cell recruitment and pro-chondrogenesis is promising for in situ articular cartilage regeneration.